Development of a sustainable society and economy based on knowledge in the United Arab Emirates - Albayati, Yas kh; Allouzi, Adel Salem; Abdalaziz, Maha Mustafa Omer; AL-Ali, Maytha; Yas, Harith (International Journal of Innovative Research and Scientific Studies, 2025)
This study sheds light on building a knowledge-based society and economy in the United Arab Emirates, where knowledge has become one of the most important factors in determining human development and comprehensive long-term economic growth. This has led the country to move towards achieving sustainable development based on knowledge; therefore, the study will focus on examining and explaining the most important pillars mentioned in the United Nations reports, in the areas of learning and transformation, and the extent to which they have been achieved on the ground, as well as the most prominent challenges faced by the country in the field of planning and implementation. The study noted that the UAE had made great and strenuous efforts to achieve its future vision of being the first country in the world by the year 2071. Just as it has made generous investments in financing education at all levels, communications infrastructure and services, science and technology, and innovation, supported by modern laws and legislation, to achieve the well-being and happiness of its citizens and to transition them to the world of knowledge, innovation, and entrepreneurship. The study concluded that sustainable investments in education, innovation, information and communications technology, and a favorable economic and institutional environment have led to an increase in the use and creation of knowledge in economic production, as recognized by international reports and indicators that placed the UAE among the top ten globally in 24 economic competitiveness indicators during the year 2020. This was achieved by analyzing the UAE's performance within the most prominent modern indicators, in terms of the Global Competitive Readiness Index, global innovation, doing business, education, research, and others, which required a presentation of the most prominent challenges facing decision-makers in this field. The study concluded by developing practical recommendations according to the field reality and the requirements of international organizations.